Development of a Volume of Fluid Method for Computing Interfacial Incompressible Fluid Flows (Communications in Computational Physics, 2020)
This study is aimed to develop a volume of fluid (VOF) method to capturethe free surface flow. The incompressible two-phase flow is computed by second-orderAdams-Bashforth algorithm with a uniform staggered Cartesian grid arrangement.The tangent of hyperbola for interface capturing (THINC) scheme and weighted linearinterface calculation (WLIC) based geometrical reconstruction procedure have beenimplemented in the operator-splitting method for the VOF method. The proposedVOF method preserves mass well, and the interface normal vector can be easily estimated from the level set (LS) function. The LS function, which is a continuous signeddistance function around the interface, is represented by solving the re-initializationequation. Numerical results using the present scheme are compared with experimental data and other numerical results in the Rayleigh-Taylor instability, dam-break flow,travelling solitary wave, Kelvin-Helmholtz instability, rising bubble and merging bubble problems. We also present numerical results in detail between computations madewith the proposed VOF method and computations made with the conventional LSmethod.
Keywords: Volume of fluid; free surface flow; THINC; WLIC; level set function.